Morphometric and topographic-anatomical features of the suprahyoid triangle of the anterior cervical region in the fetal period of human ontogenesis - O. V. Tsyhykalo; P. P. Perebyjnis (Морфологія, 2020)
Background. The study of the features of spatio-temporal transformations and the variant anatomy of the suprahyoid region (SHR), the clarification of the critical periods of development and topography of its structures in the fetal period of intrauterine development (IUD) is an important area of morphological research, the development of which contributes to the improvement of methods of prevention, early diagnosis and effective correction of congenital malformations and acquired diseases of the human neck and face. Objective. To find out the dynamics of morphometric and topographic-anatomical changes of the suprahyoid triangle of the anterior cervical region in human fetuses. Methods. 61 specimens of human fetuses 160.0-480.0 mm of parieto-coccygeal length (TCD) (4-10 months of VUR) were investigated, among which 34 were male and 27 were female. A set of methods of morphological research was applied, which included anthropometry, morphometry, X-ray techniques, preparation, three-dimensional reconstruction, statistical analysis. Results. It was found that the anterior angle of SHR in males decreases slightly during the fetal period of IUD, except for dolichomorphic objects, which tend to increase from the middle of the fetal period, while in females – almost unchanged in mesomorphic objects. In mesomorphic males and dolichomorphic females, the anterior angle of the SHR decreases at 7th month of IUD, while in brachymorphic females it increases. The length of the lateral and posterior borders, anterior-posterior length and area of SHR tend to decrease in male brachymorphic fetuses. In dolichomorphic female fetuses, it decreases by the 6th month of IUD with subsequent growth by the end of the fetal period of development. Irregular temporal dynamics of changes in these morphometric parameters of SHR is observed in dolichomorphic male fetuses and in brachymorphic female fetuses, where accelerated growth was detected in the 6th month of IUD and slowed down during the 7th month of development. Conclusion. The critical periods of morphogenesis of the SHR of human fetuses – the time of the change in the growth rate of the region depending on gender and constitutional type – are 6-7 months of IUD, which may indicate the formation of variants of the structure during this period, and the possible occurrence of congenital defects of the neck and maxillofacial region.